Northern priazov region in the period of growth of Tue civil war (november 1918 - march 1919) - Volodymyr Romantsov (Cхід)
The article focuses on issues conserving the position of northern Priazov region in the period of growth of the civil war. It also analyses the problems of military opposition in November 1918 - march1919 inPriazov region. The article highlights the role of Makhnovskiy`s movement, Greek military groups, soviet union troops, Denikin`s soldiers in the civil war of the period conserved on the territory of Mariupol country.